A case study of rupture in 110 kV overhead conductor repaired by full-tension splice. (January 2020) - Zhang, Tao; Zheng, Wencheng; Xie, Yue; Yuan, Junjian; Xu, Tao; Wang, Pengyu; Liu, Gang; Guo, Deming; Zhang, Gengbin; Liang, Yongchun
Highlights: An electromagnetic FEA model of ACSR repaired by full-tension splice is established. The cause of high temperature in repaired ACSR is analyzed. A structure FEA model of steel in repaired ACSR considering thermal effect is built. The relationship between tensions and temperatures causing ACSR rupture is discussed. The rupture risk of repaired ACSR will be likely to increase with increased time. Abstract: Rupture accidents of overhead conductors may occur due to its complex operating environment. If wires rupture happens, the overhead conductors can be repaired by full-tension splice (FTS) in practical engineering to restore the mechanical strength and ampacity required. However, with time increases, ageing will occur on the overhead conductors. There may exist potential of rupture in the repaired segment of the conductor. Once the conductor is broken, the reliability of transmission line will be seriously destroyed. Therefore, it is of great importance to investigate the rupture reason and process of conductor repaired by FTS. In this paper, a rupture accident of 110 kV overhead conductor repaired by FTS is discussed. Firstly, the fractography analysis for the conductor sample is conducted, and the rupture reason is preliminarily inferred according to the rupture feature of the sample. Then, the current density distributions in the repaired segment of new conductor and aged conductor are compared by a finite element analysis (FEA) model of electromagnetic field. Also, the reason of high temperature produced in the conductor sample during rupture process is determined. Subsequently, to analyze the relationship between temperature and equivalent plastic strain, a FEA model of structure field for the steel core of conductor is established. Finally, combined with the fractography test results and simulation results, the rupture mechanism of conductor repaired by FTS is summarized in detail. The analytical method and conclusions proposed in this paper can provide references and suggestions for the study of similar conductor rupture accident and optimization of repaired process.